THE APPLICATION OF PERSONAL HYGIENE WAITERS IN RESTAURANT AT THE ROYAL ASNOF HOTEL PEKANBARU - Nurita, Riau; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hospitality is a commercial business that provides accommodation facilities such as lodging and food and beverage service facilities. Hospitality industry is a commercial industry that operates in the field of services that is very influential on the development of tourism in Indonesia. Personal hygiene is an effort made by someone to maintain and care for their health by maintaining individual hygiene in order to control the environmental conditions of health. This research was conducted at the Royal Asnof Hotel Pekanbaru Restaurant which is located on Jalan Jl. Tuanku Tambusai No.106 Pekanbaru City. This hotel was chosen as a place of research because in it there is a modern nuanced restaurant that is very attractive to guests because of the significant increase in the number of guest visits each year so it needs to be seen how the application of personal hygiene waiters. This research purpose to determine the application of personal hygiene waiters in the Hotel Royal Asnof Hotel Pekanbaru. This research uses a qualitative method in which the data obtained are analyzed based on the ability of the investigator's reasoning in connecting information, facts and data by presenting observations, interviews and analyzing problems found in the field, so that a clear picture of the object under research can be obtained and can be obtained conclusions drawn. Based on the results of research that has been done, for the whole of the results of observation and interview answers said that based on the results of the study it can be concluded that the Application of Personal Hygiene Waiters in the Hotel Royal Asnof Hotel Pekanbaru is not in accordance with existing standards. Keywords :Personal Hygiene, Waiters, Restaurant, Hospitality